An Analysis of Digital Emotional Intelligence: Can AI Accurately Interpret Human Emotions? - Farhat Jabeen, (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
The way individuals look for emotional support has changed as a result of the growing number of AI-powered companions in digital environments; the emergence of AI-powered companions has revolutionized online communication by providing emotional support via virtual assistants and chatbots. Although these AI systems are intended to identify and react to emotions, but to the claims that these systems are capable of accurately interpreting and reacting to human emotions, questions remain about their accuracy, moral consequences, and psychological effects. The capacity of AI companions like Replika, Woebot, and Xiaoice to identify and comprehend human emotions is investigated in this study. The study employs a qualitative research technique, analyzing online user experiences through content analysis, examining AI emotional models through a case study, and thematically analyzing conversations about ethics and governance.. The results will highlight the need for stronger ethical frameworks and more dependable emotional identification algorithms, adding to the larger conversation on responsible AI research. More insight into how AI companions might support openness, equality, and confidence in human-AI interactions while promoting emotional well-being is the ultimate objective of this research